ANALISIS AKTA PENOLAKAN HAK MEWARIS OLEH AHLI WARIS BEDA AGAMA YANG DIBUAT OLEH NOTARIS - Aulga Maya M.P. (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract This research discusses the meaning of judicial and juridical implications of the legal status of the inheritance rights of a child who is born from the unregistered marriage according to KHI. The aim of this research is to determine the meaning of judicial and juridical implications of the legal status of the inheritance rights of a child who is born from the unregistered marriage according to KHI. The method used in this research is a normative study by using conceptual approach of legislation and then assisted with legal materials that will be outlined, described, and analyzed its relationship between one and another. A child can become an heir according to Islam is based on family lineage that come from the existence of a valid marriage according to the religion. According to KHI, the validity of a marriage not only has to fulfill the requirements of valid marriage but also has to fulfill the registration of the marriage. If not, it will cause a marriage that has no legal force, and it will impact to the inheritance relationship that is not going to have a legal force as well. The implication of the juridical status of the inheritance rights of children from an unregistered marriage is there is no protection of law and justice, due to a loss of status for the child's inheritance rights. Key words: inheritance rights, heir of different religions, compilation of islamic law Abstrak Penelitian ini membahas Analisis akta penolakan warisan oleh ahli waris beda agama yang dibuat di hadapan notaris dan pertimbangan hakim Pengadilan Agama Jakarta dalam putusannya Nomor 1578/Pdt.G/2010/PA.JT untuk membuat akta penolakan hak waris oleh notaris. Penelitian ini bertujuan untuk mengetahui urgensi isi akta penolakan warisan oleh ahli waris beda agama yang dibuat di hadapan notaris menurut pertimbangan hakim Pengadilan Agama Jakarta dalam putusannya Nomor 1578/Pdt.G/2010/PA.JT. Metode yang digunakan dalam penelitian ini adalah yuridis normatif, dengan menggunakan pendekatan perundang-undangan (Kompilasi Hukum Islam dan Burgerlijk Wetboek), dan pendekatan konsep. Kemudian dibantu dengan bahan-bahan hukum yang sekunder yang menjelaskan substansi akta penolakan yang dibuat oleh Notaris. Penolakan warisan oleh ahli waris beda agama yang dibuat di hadapan notaris bagi kepentingan ahli waris yang beragama Islam adalah tidak ada urgensinya, karena pernyataan penolakan tersebut tidak mempunyai kekuatan hukum atau batal demi hukum dan dianggap akta tersebut tidak pernah ada. Kemudian dianalisis menggunakan metode Intepretasi sistematis. Hakim sebagai salah satu penegak hukum, harus benar-benar memperhatikan kepastian hukum dan keadilan atas akta berupa surat penyataan penolakan sebagai ahli waris. Kata kunci: akta penolakan hak mewaris, ahli waris beda agama, notaris